PELAKSANAAN PEMBERI BANTUAN HUKUM DIKAITKAN DENGAN UNDANG-UNDANG NO. 16 TAHUN 2011 TENTANG BANTUAN HUKUM - Iwan Wahyu Pujiarto; Syafruddin Kalo; Mohammad Eka Putra; Edy Ikhsan (Universitas Sumatera Utara, 2015)
ABSTRACT Legal aid is present to provide protection against any person or group of people can not afford, poor and blind law fairly, therefore, the Legal Aid Recipients must understand their legal rights to support the provision of legal aid. Indonesia has been working to provide protection against any person or group of poor people who lodged a lawsuit with the promulgation of the Legal Act Number 16 of 2011 regarding Legal Aid but do not go according to the rules. This manuscript discusses more about the rule of legal aid, Legal Aid legal position in the implementation of Law No. 16 Year 2011 on Legal Aid, and the factors that affect the implementation of the Legal Aid